Enhancing Capacity Building in Seaweed Cultivation System among the Poor Fishermen: A Case Study in Sabah, East Malaysia - Rosazman Hussin; Suhaimi Md. Yasir; Velan Kunjuraman; Aisah Hossin (Canadian Center of Science and Education, 2015)
Community development issues in the context of sustainable development has been given serious attention from all parties namely government and private sectors. In this case study, a member of the community who wants to succeed in their life through development programmes should have positive attitude and take steps to develop themselves, while being supported by the government. This paper discusses the establishment of capacity building programmes among a poor rural community. The main objective of these programmes is to enhance the socio-economic status of the community through seaweed cultivation. Based on this, capacity building programmes were conducted for enhancing the level of community participation and high skills for the long term in the process of modern sustainable seaweed cultivation. The study was conducted between 2011 and 2013. Interviews were carried out with local fishermen and data were analysed using qualitative analyses techniques. The findings revealed that, the introduction of seaweed cultivation using the Estate Mini System and Cluster System under the initiative by the Department of Fisheries Sabah exposed the community to new technologies such as using varieties of seeds, seeds and nursery management, fertilizing and tying of seeds, the activity of solar drying and using the casino table technique in the process of seaweed cultivation. The study is significant for the fishermen experiencing the process of lifelong learning and who can enhance their knowledge and survival skills in their respective fields of employment. Moreover, capacity building programmes could change the mind-set of the community to be more open and receive the new approaches in the production of seaweed cultivation.